Impacts of macrocyclic lactones on larval survival, growth and development of three dung beetle species (Coleoptera: Scarabaeidae). Issue 1 (12th December 2021) - Mackenzie, Sigrid L; Hall, Graham; Schaerf, Timothy M; Andrew, Nigel R
Abstract: Macrocyclic lactones (MLs) are some of the most pervasive chemicals used in cattle management to control internal parasites. However, the drenches can have a range of lethal and sublethal impacts, potentially impacting the efficiency of adult dung beetles at burying dung and negatively impacting their larval growth, development and survival. Here, we assess the impacts of adult dung beetles provisioning their larvae with cattle faecal residues containing three commonly used cattle drenches in Australia – moxidectin, abamectin and doramectin. We used the larvae of two introduced tunnelling (paracoprid) species: Onthophagus binodis and Onitis viridulus, and one introduced rolling (telecoprid) species: Sisyphus rubrus . We anticipated that dung beetle larvae feeding on dung containing an ML would have altered growth patterns to those larvae feeding on untreated dung. Further, beetle larvae exposed to an ML in the dung would have different growth patterns, depending on the time the chemical took to be excreted from the treated cattle, with the anticipation that the chemical may have a peak excretion time. We also expected that dung beetle larvae feeding on dung containing an ML would have a decreased survival rate compared to dung beetle larvae feeding on untreated dung. We found that abamectin and doramectin were more toxic to beetle larvae than moxidectin and control dung, across all three species, and these chemicals also had the greatest negative impact on larval growth and development. Abamectin excreted 7 days after treatment resulted in few live larvae. Overall, moxidectin was the least toxic ML to the larvae assessed, and generally, the drench impacts were reduced as time since exposure increased.